(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2015)
SCADA refers to the centralized systems that control and monitor the entire sites, or they are the complex systems spread out over large areas. Nearly all the control actions are automatically performed by the remote terminal units (RTUs) or by the programmable logic controllers (PLCs). The restrictions to the host control functions are supervisory level intervention or basic overriding. For example, the PLC (in an industrial process) controls the flow of cooling water, the SCADA system allows any changes related to the alarm conditions and set points for the flow (such as high temperature, loss of flow, etc) to be recorded and displayed. The aim of this thesis is, firstly to recall the basic concept of SCADA system to present the project management phase of SCADA for real time implementation and then to show the need of automation for Power Distribution Company’s (PDC) on their distribution and the importance of using computer based system tower sustainable development of their services most control action are performed automatically by RTU host control functions are usually restated to basic overriding or supervisory level intervention, a computer based power distribution automation system is than discussed, finally some projects SCADA system implication in electrical companies over the world is briefly presented.